Effect of soil conservationist systems and gypsum residue on soybean - Freitas, Leandro Alves [UNESP]; Mano de Mello, Luiz Malcolm [UNESP]; Yano, Elcio Hiroyoshi [UNESP]; Pereira, Diego dos Santos [UNESP]; Souza, Fabio Henrique de [UNESP] (Univ Federal Mato Grosso, 2016)
This experiment was obtained in the aim of studying the sequences of conservation soil management systems on soybean production attributes. The study was conducted at the experimental farm area of Research and Extension belonging to UNESP, The Solteira-SP. The experimental design was a randomized block, with four farming systems: no tillage Continuous (SPD-SPD) and alternating (SPD-CM), Cultivation Continuous minimum (CM-CM) and alternating (CM-SPD) with or without the use of plaster. were evaluated the Agronomic characteristics of soybean. The various forms and methods of soil conservation systems with use plaster were intended to improve the soil characteristics and agronomic of soybean. But this work was not possible to identify a better soil management with the use of plaster, but yes demontar that regardless of the system used, the plaster provides better physical and chemical characteristics of the soil and soybean agronomic The no tillage system continuous provide the highest values for initial and final population. The use of phosphogypsum provided only values greater the weight of 100 grains.
Keywords: agricultural gypsum; Glycine max (L.); soil management